2008
DOI: 10.1007/s00431-008-0820-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and long-term outcome of Ebstein’s anomaly based on a 26-year experience in an Asian cohort

Abstract: Ebstein's anomaly is a rare, congenital cardiac anomaly that may result in cyanosis, right heart failure, and tachyarrhythmia during the newborn stage or after adolescence. This study investigated the data of 77 patients diagnosed between 1980 and 2006 at a tertiary care center in Taiwan. Patients were grouped into either an early group or a late group. Survival declined rapidly within the newborn stage in the early group, but declined only during the third decade in the late group. Surgical results were poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Supraventricular arrhythmia was seen in 80 patients. A recent Asian cohort study of Ebstein’s anomaly found SVT in half of the patients [10]. Other series show an incidence of WPW varying from 10 to 29% of patients with Ebstein’s anomaly [3,4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Supraventricular arrhythmia was seen in 80 patients. A recent Asian cohort study of Ebstein’s anomaly found SVT in half of the patients [10]. Other series show an incidence of WPW varying from 10 to 29% of patients with Ebstein’s anomaly [3,4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that ≈50% of adult patients with EA experienced arrhythmic complications, which is consistent with previous studies. 2,4,5,16 In addition, we found the presence of fQRS to be independently associated with overall arrhythmic events, even after adjusting for relevant clinical and echocardiographic parameters.…”
Section: New Findingsmentioning
confidence: 71%
“…Although there have been some studies dealing with arrhythmic complications in adult patient groups, they only described the prevalence of a few types of arrhythmias in a limited number of patients. [2][3][4][5] Most of the previous data focused primarily on the characteristics or management of AVRT with a bypass tract. [14][15][16] In contrast, we evaluated the association between fQRS and arrhythmic risk as well as the severity of the structural abnormality.…”
Section: New Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite appropriate treatment, mortality proved to be very high in the first years of life, as has been reported previously in EA patients. 24 The cluster analysis of EA comorbidities identified 2 clearly …”
Section: Discussionmentioning
confidence: 99%